Ten years' experience with four cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone, procarbazine (BEACOPP)-escalated followed by four cycles of baseline-dose BEACOPP in patients with advanced stage Hodgkin lymphoma: a single-center, retrospective study - Belada, David; Štěpánková, Pavla; Sýkorová, Alice; Žák, Pavel; Smolej, Lukáš (Leukemia & lymphoma, 2015)
The HD-9 trial showed that eight cycles of BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone, procarbazine)-escalated led to significant improvements in response rate, progression-free survival and overall survival over COPP/ABVD (cyclophosphamide, vincristine, prednisone, procarbazine/doxorubicin, bleomycin, vinblastine, dacarbazine) therapy. This monocentric retrospective study was performed to evaluate 10 years of experience with four cycles of BEACOPP-escalated and four cycles of BEACOPP-baseline outside of clinical trials. The outcomes were assessed in 78 patients with newly diagnosed advanced stage Hodgkin lymphoma. A complete response after chemotherapy ± radiotherapy was achieved in 75 patients (96%). At the median follow-up of 74 months, the actuarial 5- and 10-year freedom from treatment failure (FFTF) rates were 91% and 89%, and actuarial 5- and 10-year overall survival rates for the entire group were 93% and 90%, respectively. These results suggest that the combination of escalated and baseline BEACOPP chemotherapy is feasible in routine practice with good efficacy and acceptable toxicity.
Keywords: Neoplasm Recurrence, Local; Vincristine; Humans; etoposid; lidé středního věku; Bleomycin; Dose-Response Relationship, Drug; bleomycin; doxorubicin; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; Female; prokarbazin; Doxorubicin; Hodgkin Disease; Prednisone; Etoposide; Time Factors; lidé; časové faktory; Hodgkinova nemoc; Adult; prednison; staging nádorů; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; vinkristin; Retrospective Studies; Adolescent; prognóza; Antineoplastic Combined Chemotherapy Protocols; Cyclophosphamide; Procarbazine; Young Adult; vztah mezi dávkou a účinkem léčiva; retrospektivní studie; Neoplasm Staging; lokální recidiva nádoru; míra přežití; mužské pohlaví; cyklofosfamid; Prognosis; následné studie; mladiství; Survival Rate